Amsterdam's Canal District : origins, evolution, and future prospects - Nijman, Jan (University of Toronto Press, 2020)
"In terms of design, scale, and blending of ecologicical and esthetic function, Amsterdam's seventeenth-century Canal District is a European marvel. Its survival for four centuries is a testament to its ingenuity, reflected in its designation as a UNESCO World Heritage Site in 2010. The Canal District today is an extraordinary example of resilient historic design and cultural heritage in a living city, but it is not without present-day challenges: in recent years, its urban ecology has become subject to severe pressures of global tourism and supergentrification. This edited volume brings together 17 reputable scholars to debate questions about the origins, evolution, and future of the Canal District. With differing approaches and perspectives on the Canal District, the contributions render a collection where the whole is much more than the sum of the parts. The book breaks new ground in our understanding of the District's historic design, its evolution over four hundred years, and the fundamental issues in strategies and policies towards the future. While the main focus is clearly on Amsterdam, the discussions have an important bearing on urban historic preservation elsewhere, and on questions about enduring urban design."--